Sustainability of locally driven centres for those affected by dementia: a protocol for the get real with meeting centres realist evaluation. Issue 5 (2nd May 2022) - Morton, Thomas; Evans, Shirley B; Brooker, Dawn; Williamson, Tracey; Wong, Geoff; Tinelli, Michela; Frost, Faith; Bray, Jennifer; Hullah, Nigel
Abstract : Introduction: Improving support for people with early to moderate dementia to live at home in their communities is a global public health goal. Community adult social care is not robust in many parts of the UK, however, with the pandemic increasing pressure on services for this population. Community-led interventions can play a key role in supporting people postdiagnosis, helping delay decline, but many interventions struggle to sustain beyond 1–2 years. Meeting Centres (MCs) are one such intervention, which many UK community groups find attractive and achievable. However, it is not understood how these communities can ensure they are putting in place strategies that will help them sustain in the longer term, beyond start-up phase. Methods and analysis: This realist evaluation aims to understand the factors affecting sustainability of MCs in rural areas and learn lessons from MCs that have sustained beyond 3 years. Data will be collected using mixed methods: interviews and group discussions with stakeholders involved at every level in three case study locations in England and Wales, analysed with Soft Systems modelling; a Discrete Choice Experiment exploring what people across the UK value and are willing to pay for MCs, analysed with regression modelling. All data will be synthesised using a Realist logic of analysis to build a theoretical model of how, why, for whom, in what contexts and to what extent MCs can be successfully implemented for the long term. Ethics and dissemination: As participants may lack capacity for informed consent, favourable ethical opinion was received from a Health Research Authority research ethics committee. Resulting recommendations will be of interest to stakeholders including those commissioning, planning, running, supporting or attending MCs, as well as policy-makers and healthcare professionals. Knowledge will be shared with emerging MCs to help accelerate scale up of this intervention.